The Human Face of Digital Preservation: Organizational and Staff Challenges, and Initiatives at the BibliothÃ¨que nationale de France - Emmanuelle BermÃ¨s; Louise Fauduet (International Journal of Digital Curation, 2011)
The process of setting up a digital preservation repository in compliance with the OAIS model is not only a technical challenge: libraries also need to develop and maintain appropriate skills and organizations. Digital activities, including digital preservation, are nowadays moving into the mainstream activity of the Library and are integrated in its workflows.